2016
DOI: 10.1186/s40942-016-0049-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of optical coherence tomography in Alzheimer’s disease

Abstract: BackgroundAlzheimer’s disease (AD) is the most common cause of dementia and its incidence is increasing worldwide along with population aging. Previous clinical and histologic studies suggest that the neurodegenerative process, which affects the brain, may also affect the retina of AD patients.Main bodyOptical coherence tomography (OCT) is a non-invasive technology that acquires cross-sectional images of retinal structures allowing neural fundus integrity assessment. Several previous studies demonstrated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 61 publications
2
26
0
2
Order By: Relevance
“…As the severity of cognitive impairment can be measured with MMSE score, the association between the OCT parameters and this cognitive test can give us useful information for the clinical valuation and monitoring of patients with ATD 25. In our study, we found a significantly higher positive correlation between the MMSE score and superficial retinal vascular density and CT.…”
Section: Discussionsupporting
confidence: 56%
“…As the severity of cognitive impairment can be measured with MMSE score, the association between the OCT parameters and this cognitive test can give us useful information for the clinical valuation and monitoring of patients with ATD 25. In our study, we found a significantly higher positive correlation between the MMSE score and superficial retinal vascular density and CT.…”
Section: Discussionsupporting
confidence: 56%
“…Converging data on AD-related retinal abnormalities encouraged investigators to develop noninvasive retinal imaging modalities in order to detect and measure these anatomical changes in living patients. This was initially attempted using blue-light high-resolution photography by Tsai et al ( 63 ), and later advanced to utilizing cross-sectional imaging by OCT ( 34 , 37 , 67 70 ). OCT findings in MCI, AD, and PD patients along with their correlations with cognition and vision are described subsequently and summarized in Tables 1 and 2 .…”
Section: Retinal Pathology In Admentioning
confidence: 99%
“…In addition to the above findings, studies have demonstrated a link between OCT measures and psychological tests, such as the mini‐mental state examination, that are utilised to assess cognitive function . The retinal nerve fibre layer and macular parameters have been shown to be correlated with mini‐mental state examination scores.…”
Section: Alzheimer's Diseasementioning
confidence: 88%